Understanding forecast failure of ESTAR models of real exchange rates - Daniel Buncic (Economics and Econometrics Research Institute (EERI), 2009)
The forecast performance of the empirical ESTAR model of Taylor, Peel and Sarno (2001) is examined for 4 bilateral real exchange rate series over an out-of-sample eval-uation period of nearly 12 years. Point as well as density forecasts are constructed, considering forecast horizons of 1 to 22 steps head. The study finds that no forecast gains over a simple AR(1) specification exist at any of the forecast horizons that are considered, regardless of whether point or density forecasts are utilised in the evaluation. Non-parametric methods are used in conjunction with simulation techniques to learn about the models and their forecasts. It is shown graphically that the nonlinearity in the point forecasts of the ESTAR model decreases as the forecast horizon increases. The non-parametric methods show also that the multiple steps ahead forecast densities are normal looking with no signs of bi-modality, skewness or kurtosis. Overall, there seems little to be gained from using an ESTAR specification over a simple AR(1) model.
Keywords: C22; C52; C53; F31; F47; 330; Purchasing power parity; regime modelling; non-linear real exchange rate models; ESTAR; forecast evaluation; density forecasts; non-parametric methods